A dynamic programming-based model for determining the optimum workplace size. - Martinez, Iris Ann G. (Journal of the philippine institute of industrial engineers)
The determination of the appropriate workforce size as part of production planning can be approached using a variety of mathematical tools. There are techniques based on Linear Programming while some are based on trial-and-error. In practice, the trial-and-error or informal techniques are more commonly used. This is because computations are easily done. However, because informal techniques are based on rules of thumb only, it is very rare that cost-wise optimum solutions are reached.